On the Effectiveness of SB1070 in Arizona - Catalina Amuedo-Dorantes; Cynthia Bansak; Allan A. Zebedee (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
We investigate the effectiveness of Arizona's omnibus immigration law SB1070, which made it a misdemeanor crime for an alien to not carry proper documentation and asked police to determine the immigration status of any person suspected of being an illegal alien during a lawful stop. We find that SB1070's enactment coincided with the stalling to slight recovery of the share of non-citizen Hispanics in Arizona three years after the enactment of an employment verification mandate to all employers. Yet, its effectiveness in reducing the share of likely unauthorized immigrants has been minimal and questions the merit of the law.
Keywords: F23; J61; R12; 330